Vaccination for prevention of hearing loss: a scoping review - Mira Johri; Shoghig Téhinian; Myriam Cielo Pérez Osorio; Enis Barış; Brian Wahl (Communications Medicine)
Abstract Background Infectious diseases in childhood and adolescence are significant and often preventable causes of hearing loss, especially in low- and middle-income countries. We conducted a scoping review to examine the extent, range and nature of available evidence on the role of vaccination for prevention of hearing loss worldwide. Methods We reviewed the published scientific literature to identify studies providing quantitative information on the relationship between vaccination and hearing loss. We searched four databases: MEDLINE, EMBASE, Cochrane Library and Global Index Medicus. No date, language, or geographical restrictions were imposed. Two independent reviewers assessed eligibility and charted data. Results Here we show that vaccination may be a key, underexploited strategy for primary prevention of child and adolescent hearing loss. Although the important contributions of rubella and meningitis vaccinations to hearing loss prevention are widely recognised, we identify 26 distinct known or potential infectious causes of hearing loss that are preventable or possibly preventable through vaccination. Notwithstanding, we find a dearth of empirical evidence on the impacts of vaccination on hearing loss prevention. In addition, the review identifies no research from low- and middle-income countries, which bear the overwhelming burden of child and adolescent hearing loss. Finally, it shows that numerous vaccines that address priority infectious diseases relevant to hearing loss are in development and could be brought into use. Conclusions We recommend strategic investment in research concerning vaccination as a strategy for primary prevention of child and adolescent hearing loss.